Understanding Open-Vent Volcanism and Related Hazards 2013
DOI: 10.1130/2013.2498(03)
|View full text |Cite
|
Sign up to set email alerts
|

Continuous subsidence associated with the long-lasting eruption of Arenal Volcano (Costa Rica) observed by dry-tilt stations

Abstract: Arenal volcano is a small (~1750 m a.s.l., ~10 km 3) stratovolcano that continuously erupted between July 1968 and October 2010. During this long-lasting eruption (over 42 years), a large volume of material-about 5.6 x 10 8 m 3 of dense rock equivalent-has been extruded and has produced a thick and extended lava field, mainly on the western flank of the edifice. Measurements of ground deformation obtained using a network of dry-tilt stations are presented for the period 1986-2000. They show a continuous subsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…We limit the extent of the output velocity field using a threshold of the combined rms on the north, east and up components set at 1 σ < 5 cm, as well as the limit of the InSAR coverage. The deformation pattern at Arenal volcano presented here is much more complex than described by previous papers (Ebmeier et al 2010;Avard et al 2012;Feng et al 2012;Mora et al 2013), yet still in agreement with them. Fig.…”
Section: Spatial and Temporal Integrationsupporting
confidence: 92%
See 4 more Smart Citations
“…We limit the extent of the output velocity field using a threshold of the combined rms on the north, east and up components set at 1 σ < 5 cm, as well as the limit of the InSAR coverage. The deformation pattern at Arenal volcano presented here is much more complex than described by previous papers (Ebmeier et al 2010;Avard et al 2012;Feng et al 2012;Mora et al 2013), yet still in agreement with them. Fig.…”
Section: Spatial and Temporal Integrationsupporting
confidence: 92%
“…They disregard most of these as primary mechanism and suggest that the mechanism causing the observed ground deformation is a gravity driven instability. Mora et al (2013) used a dry-tilt network around the volcano between 1986 and 2000 that showed a tilt toward the edifice, they reproduced the observed tilt data by loading the weight of the 1988-2000 emplaced lava field on an elastic basal layer. The addition of the deflation of a shallow-seated magma reservoir did not improve the quality of the fit to the observations.…”
Section: Arenal Volcanomentioning
confidence: 90%
See 3 more Smart Citations